Problematika Peserta Didik dalam Operasi Hitung di Kelas 1 SD Negeri 80 Muara Bulian - Sholikha, Imroatu; Nurhalizah, Siti; Pakpahan, Gritia Putri; Sari, Regita Eka Puspita (Lembaga Yasin AlSys, 2023)
Mathematics is widely used in various fields of life. However, in reality, activities for every individual cannot always run as they should, there will be some problems, even in learning mathematics. This situation is influenced by a person's comprehension of a lesson. Examples of problems in learning mathematics can be seen in the technique of adding derivatives, which is the result of dozens or tens or two-digit numbers (often called storing numbers), which results in incorrectly determining the results of further arithmetic operations. This research activity uses a qualitative approach. When referring to the problems studied, using qualitative methods makes it possible to gain an understanding of the reality on the ground. Based on the results of observations at SDN 80 Muara Bulian in class 1C in learning to count there were some students who wrote numbers from below which should have been from above so that they looked neat in writing and the prohibition on writing numbers starting from the early grades, so that later students could write numbers correctly. Correct. Learning withdrawal is an activity that is accompanied by symptoms that hinder achieving the desired goal, so efforts are needed to overcome these symptoms. Completion of learning is a disability or imperfection that causes a person to have difficulty carrying out learning activities so that the learning process becomes ineffective. Expansion of learning is a collection of various disorders that vary in manifestations, which are inability to listen, speak, read, write, think, and do arithmetic. Students with learning difficulties tend to have low interest and motivation in learning mathematics, this is shown by students who are not active during class learning, they tend not to want to ask questions when the teacher gives them the opportunity to ask questions. In addition, students are lazy to do exercises or assignments given by the teacher. Students who have difficulties are also often noisy in class and do not pay attention to the teacher's explanation.